2018
DOI: 10.15356/2076-6734-2018-1-65-77
|View full text |Cite
|
Sign up to set email alerts
|

Methane in Ground Ice and Frozen Sediments in the Coastal Zone and on the Shelf of Kara Sea

Abstract: Degradation of permafrost on the continental shelf and shores of the Arctic seas may be a main cause of the methane emission to the atmosphere from marine sediments. To quantify this effect it is necessary to have reliable data on the methane content in the underground ice and frozen Quaternary deposits. Samples of frozen (permafrost) sediments and ground ice, taken in three reference coastal sections made in the Mid-and Late Pleistocene coastal exposures and on the Kara sea shelf, were collected and studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…It also provides an input of methane to δ 13 C as low as -87‰, and values from -60‰ to -65‰ were reported for 10 gas-bearing fields in West Siberia at depths below 700 m [25]. The gas from shallower permafrost studied in Russia and Canada, which was both degassed from sediments [17,20] and emitted from accumulations [5,12,26], was mostly biogenic. Methane seeps in Alaska were reported to be thermogenic and of mixed origin [3], which was strongly distinct from the surficial methane sources in closed talik.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…It also provides an input of methane to δ 13 C as low as -87‰, and values from -60‰ to -65‰ were reported for 10 gas-bearing fields in West Siberia at depths below 700 m [25]. The gas from shallower permafrost studied in Russia and Canada, which was both degassed from sediments [17,20] and emitted from accumulations [5,12,26], was mostly biogenic. Methane seeps in Alaska were reported to be thermogenic and of mixed origin [3], which was strongly distinct from the surficial methane sources in closed talik.…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies showed that epigenetic permafrost always contains methane in an average concentration of 2.7 mg CH 4 m −3 (up to 47.4 g CH 4 m −3 ) of frozen sediment as opposed to syngenetic permafrost, which in most cases did not have any detectable methane [17,18]. High concentrations of methane in permafrost deposits were found in redeposited and refrozen sediments of drained thaw lake basins in Central Yakutia [19], whereas moderate concentrations were detected in loams and the segregation ice of marine deposits on the Yamal Peninsula [20]. Methane in permafrost could be produced at temperatures below zero by methanogenic archaea [21], and it could be converted to interpore gas hydrate [22].…”
mentioning
confidence: 99%
“…The lower part of profile in this area is composed by Late Pleistocene saline marine clays with the inclusion of sand layers formed during Marine Isotope Stage (MIS) 5 (127-71 kyr BP cal) [38]. The layer has no visible organic inclusions, the mean total organic carbon (TOC) is 0.84% [27]. Marine clays were freezing epigenetically as a result of retreating sea.…”
Section: Study Areamentioning
confidence: 98%
“…The upper part of the profile is composed of alluvial lacustrine sands and sandy loams formed during MIS 3 (57-24 kyr BP cal) and MIS 2 (24-11 kyr BP cal) [34]. These sediments contain visible organic detritus, but mean organic content is only 0.34% [27]. The thin layer of Holocene sediments is mostly represented by aeolian sands and peatlands tops the profile.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation